The cooperative principle of concern for community in legislation. The Education and Promotion Fund as the main instrument for its implementation - Hernández Cáceres, Daniel (REVESCO. Revista de Estudios Cooperativos, 2023)
Following the recognition of the cooperative principle of concern for community by the International Cooperative Alliance, through the Declaration on the Cooperative Identity of 1995, the various cooperative laws that have subsequently been enacted, as well as those previous laws that have been amended, have had to incorporate new guidelines aimed at complying with this principle. This paper will examine how the cooperative principle of concern for community has been incorporated into Spanish, national and regional positive cooperative law, as well as in comparative law. Through this analysis we will try to verify whether the legislations have been conditioned by the principle of concern for community and oblige cooperatives to comply with it, or whether, on the contrary, the cooperative principle of concern for community has not been implemented and lacks legal effectiveness.
Keywords: Sustainable development; Social responsibility; Sustainability; Good governance; Stakeholders